Modulation of endoplasmic reticulum stress–induced insulin resistance by the low-carbohydrate high-fat ketogenic diet - Eldakhakhny, Basmah M.; Ghoneim, Fatma M.; Almoghrabi, Yousef M.; Ajabnoor, Ghada; Alandejani, Faisal; Abo El-Khair, Salwa M.; Elsamanoudy, Salma A.; Shamrani, Taghreed; Siddiqui, Moaaz A.; Elsamanoudy, Ayman Z. (Frontiers in Nutrition, 2026)
This review aimed to investigate the relationship between endoplasmic reticulum (ER) stress, insulin resistance, and the potential mitigating effects of a low-carbohydrate, high-fat diet, Ketogenic diet (LCHF-KD). A detailed literature search using databases to achieve a comprehensive overview. The keywords of the search were “endoplasmic reticulum stress,” “insulin resistance,” “metabolic syndrome,” and “low carbohydrate-high fat diet, molecular mechanism, Biochemical effects, Metabolic effects, Signaling pathways.” Insulin resistance is a metabolic disorder characterized by decreased cell sensitivity to insulin, resulting from the interplay between genetic and environmental factors. It can act as both a result and trigger of uncontrolled endoplasmic reticulum stress. This condition is associated with several disruptions, including impaired endoplasmic reticulum-mitochondrial transport, disordered signaling pathways, macrophage dysfunction, autophagy, immune function, inflammatory responses, dysregulation of antioxidant responses, and altered expression of genes involved in the endoplasmic reticulum stress response. LCHF-KD has been shown to alleviate insulin resistance associated with endoplasmic reticulum stress. Finally, it is concluded that ER stress plays a crucial role in the development of insulin resistance and metabolic diseases, including type 2 diabetes and obesity. Therapeutic strategies, including chemical chaperones and unfolding protein response (UPR) modulators, were used to alleviate ER stress. Dietary interventions, such as the low-carbohydrate, high-fat ketogenic diet (LCHF-KD), also reduce ER stress and improve metabolic health by modulating inflammation and oxidative stress. Combining these with conventional dietary therapies and personalized medicine approaches may enhance treatment outcomes and prevent the progression of metabolic disorders.